Works councils and workplace health promotion in Germany - Jirjahn, Uwe; Mohrenweiser, Jens; Smith, Stephen (Bonn, 2019)
"From a theoretical viewpoint, there can be market failures resulting in an underprovision of occupational health and safety. Works councils may help mitigate these failures. Using establishment data from Germany, our empirical analysis confirms that the incidence of a works council is significantly associated with an increased likelihood that the establishment provides more workplace health promotion than required by law. This result also holds in a recursive bivariate probit regression accounting for the possible endogeneity of works council incidence. Furthermore, analyzing potentially moderating factors such as collective bargaining coverage, industry, type of ownership, multi-establishment status and product market competition, we find a positive association between works councils and workplace health promotion for the various types of establishments examined. Finally, we go beyond the mere incidence of workplace health promotion and show that works councils are positively associated with a series of different measures of workplace health promotion."